The Importance of Hadith Learning in the Formation of Islamic Law - Yusuf, Muhammad Fajri; Siregar, Bona Bargot Riezky Nagabe (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to examine the importance of learning hadith in the formation of Islamic law through a qualitative approach. This study uses a qualitative method, with a literature review approach to explore the view of how the learning of hadith contributes to the formation of Islamic law in accordance with the times. The findings of the study show that hadith learning based on understanding sanad, matan, and historical context can produce more relevant and applicable legal interpretations. In addition, a wrong or in-depth understanding of hadith can lead to abuse and errors in the determination of the law. Deep learning of hadith is not only to know the history or story of the life of the Prophet Muhammad, but also to understand the ways in which the Prophet applied the law in various aspects of daily life.